EDTA Shuttle Effect vs. Lignosulfonate Direct Effect Providing Zn to Navy Bean Plants (Phaseolus vulgaris L ‘Negro Polo’) in a Calcareous Soil - Cieschi, María T.; Benedicto, Ana; Hernández-Apaolaza, Lourdes; Lucena, Juan J. (Frontiers in Plant Science, 2016)
Zn-Lignosulfonates (LS) fertilizers are used as an eco-friendly alternative to chelate formulations. The mechanisms of Zn release in the rhizosphere by both types of products are compared. The ability to provide Zn to Phaseolus vulgaris L of non-modified and chemically modified ZnLS and ZnEDTA is compared in a hydroponic assay. Stable isotope 67Zn was used to study Zn source (fertilizer, ZnFer, or native, ZnNat) uptake and distribution in plants in two soil pot experiments. ZnEDTA was the best treatment to provide both ZnFer and ZnNat to navy bean plants. A shuttle effect mechanism and an isotopic exchange may occur. ZnLS from eucalyptus (ZnLSE) provides more Zn to the plant than LS from spruce (ZnLSS). Chemical modifications of ZnLSE does not improve its efficiency. A double dose of ZnLSE provides similar ZnFer in leaves and similar soluble ZnFer content in soil than ZnEDTA. A model for the Zn fertilizers behaviour in the soil and plant system is presented, showing the shuttle effect for the synthetic chelate and the direct delivery in the rhizosphere for the Zn-LS complex.